Unveiling symbolic meaning: A semiotic analysis of ritual objects in the Munggah Suwunan tradition - Wahyuni, Leny Sri; Musdalifah, Lula (citeus, 2025)
Munggah Suwunan or Munggah Mulo tradition, still practiced in Javanese communities like Warugede and Durajaya in Cirebon. The tradition is significant in Javanese culture because it symbolizes important values and beliefs deeply rooted in the community. It represents more than just a construction milestone; it embodies spiritual and cultural connections to life, nature, and God. The act of raising the highest roof beam is seen as a moment of gratitude and reverence, where participants pray for blessings, prosperity, and protection for the household. Therefore, this study aims to analyze the meaning of denotation and connotation as well as the myths contained in the objects used in Munggah Suwunan tradition. This is a qualitative descriptive research method. Through a semiotic analysis based on Roland Barthes’ theory, this study explores the denotative and connotative meanings of the fourteen objects used in the tradition which convey deep symbolic meaning related to human life, reflecting values of spirituality, patriotism, and communal support, then revealing myths of gratitude, prayers, and hopes for blessings and prosperity. By performing Munggah Suwunan, the community not only upholds local wisdom and spiritual practices but also strengthens social bonds, reflecting the Javanese philosophy of harmony between humans and their environment. This ritual thus holds a dual significance: preserving cultural identity and maintaining the spiritual well-being of individuals and their homes.